Thermal efficiency in hybrid (Al2O3-CuO/H2O) and tri-hybrid (Al2O3-CuO-Cu/H2O) nanofluids between converging/diverging channel with viscous dissipation function: Numerical analysis - Adnan,; Guedri, Kamel; Raizah, Zehba; Tag-Eldin, Elsayed; Ashraf, Waqas; Khan, Umar; M. Galal, Ahmed (Frontiers in Chemistry, 2022)
Heat transfer and energy storage remain a core problem for industrialists and engineers. So, the concept of new heat transfer fluids, namely, nanofluids and hybrid nanofluids, has been introduced so far. Recently, a new third generation of heat transfer fluids has been developed known as modified hybrid nanofluids (MHNs), synthesized by ternary nanomaterials and the host fluid. Therefore, the study was conducted to investigate the energy storage efficiency between (Al2O3-CuO-Cu/H2O)mhnf and (Al2O3-CuO/H2O)hnf in the presence of novel viscous dissipation effects. The problem is developed for a channel with stretchable walls via thermophysical attributes of binary and ternary guest nanomaterials and the host liquid. The model is tackled numerically and furnished results for the dynamics, most specifically energy storage efficiency in (Al2O3-CuO-Cu/H2O)mhnf. It is examined that the third generation of heat transfer fluids (Al2O3-CuO-Cu/H2O)mhnf has high thermal energy storage efficiency than traditional nano and hybrid nanofluids. Therefore, these new insights in heat transfer would be beneficial and cope with the problems of energy storage in the modern technological world.